THE 12TH SARAWAK STATE ELECTION: A STYLISTIC ANALYSIS OF BANNERS & POSTERS OF THE RULING AND OPPOSITION PARTIES - Siti Haslina, Hussin; Jamilah, Maliki; Malia, Taibi (UNIVERSITI MALAYSIA SABAH, 2023)
This study analysed selected election banners and posters in Kuching and Kota Samarahan areas during the 2021 Sarawak State Election. Crystal and Davy’s framework was used to analyse the graphetic, typographical, and textual features of the election poster and banners. A total of 20 posters and 12 banners were photographed, studied, and analysed. The results show that at the graphetic level, the ruling party used new colour and logo as a new identity. Whereas the opposition parties use many colours which confused the electorate. The ruling and opposition parties similarly utilize photos of the candidates and the logo of the party. Typographically, the opposition parties use more capital letters in their messages. The syntactic features of the ruling party are clear, precise, factual, and mostly in declarative moods. The stylistic analysis shows there are similarities in the strategies used in the election banners by the ruling and opposition parties. Nevertheless, they share differences in the strategies for election banners. Keywords: stylistic analysis, election posters, election banners, Sarawak, Malaysia